Statistical Analysis of Informal Settlements and Environmental Management in Mbale Municipality, Uganda - Mustafe, Hassan Abdi; Nafiu, Lukman Abiodun; George Stanley, Kinyata (International Journal of Research in Engineering, IT and Social Sciences, 2021)
The study examined the impact of informal settlement on environmental management. Selfadministered questionnaire and interview guide were used to gather information from one hundred and forty-five household respondents and seven key informants in Namatala ward. The data collected were then analysed with the aid of Statistical Package for Social Sciences. The study identified the socioeconomic effects of informal settlements which include road inaccessibility, poor waste collection, and poor waste disposal, inadequate open space for dumping, and rapid production of waste and community conflicts. Results indicated that environmental management in informal settlements depend on community role. Findings have shown that a strong positive relationship exist between community role and environmental management which is statistically significant. Results have also revealed that community role and education level of community have 42.2% effect on environmental management in informal settlement which is statistically significant. The study recommends that community should play roles in managing the environment and identify possible strategies to improve environmental management in informal settlements. Therefore, there is a need to sensitize the local community on environmental education in order to improve environmental management in informal settlements. Local governments should implement community infrastructure upgrading. NGOs and local governments need to conduct domestic waste minimization campaign. There is also need to provide economic incentives to the poor in urban community. Local officials at all levels should cooperate so as to make easy the inspection of developments during construction.